(untitled) (Fiep Bulletin - online, 2017)
This paper presents a proposal to develop an application program for smartphones to be used as an electronic votingsystem in problem solving activities in various curricular subjects. This theoretical research aimed on both electronic and low-costvoting systems and their respective contributions to improvements in the teaching and learning processes. It approaches theinsertion of mobile phones and smartphones in classes, as well as the relation of response systems with interactive teachingmethodologies, in order to inform the reader about the importance of voting systems and their potentialities for the educationalprocess.